2022
DOI: 10.1038/s41598-021-04571-3
|View full text |Cite
|
Sign up to set email alerts
|

Planning evaluation of a novel volume-based algorithm for personalized optimization of lung dose in VMAT for esophageal cancer

Abstract: Radiotherapy treatment planning (RTP) is time-consuming and labor-intensive since medical physicists must devise treatment plans carefully to reduce damage to tissues and organs for patients. Previously, we proposed the volume-based algorithm (VBA) method, providing optimal partial arcs (OPA) angle to achieve the low-dose volume of lungs in dynamic arc radiotherapy. This study aimed to implement the VBA for esophageal cancer (EC) patients and compare the lung dose and delivery time between full arcs (FA) witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Several randomized controlled studies have demonstrated that DCCRT for ESCC may offer a comparable survival to standard surgery, 4,16 especially in patients who respond to chemoradiation. Although modern radiotherapy techniques using IMRT or VMAT which provide significantly better normal tissue sparing have been widely applied in recent years, the optimal radiation dose for esophageal cancer still remains controversial 8,10,17–20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several randomized controlled studies have demonstrated that DCCRT for ESCC may offer a comparable survival to standard surgery, 4,16 especially in patients who respond to chemoradiation. Although modern radiotherapy techniques using IMRT or VMAT which provide significantly better normal tissue sparing have been widely applied in recent years, the optimal radiation dose for esophageal cancer still remains controversial 8,10,17–20 …”
Section: Discussionmentioning
confidence: 99%
“…Although modern radiotherapy techniques using IMRT or VMAT which provide significantly better normal tissue sparing have been widely applied in recent years, the optimal radiation dose for esophageal cancer still remains controversial. 8,10,[17][18][19][20] F I G U R E 2 Radiation dose-survival curve of the patients receiving DCCRT. Based on the radiation dose, patients were divided into the 45-50, 50-55, 55-60 and 60-65 Gy groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation